Classical Cooperative Learning Model for Reading Classic Literature: Enhancing Student Independence through Self-Regulation - Umar Manshur; Nur Hadi; Mowafg Abrahem Masuwd (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2025)
This study aimed to analyze the cooperative learning model developed by teacher at the Miftahul Midad Islamic Boarding School Indonesia, which combines classical learning to enhance students' ability to read classical texts and foster their independence through self-regulation. The research employed a qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation studies. The researchers followed several stages of data analysis, including data reduction, data presentation, formulating preliminary conclusions, and verification activities. The findings revealed four stages of classical cooperative learning that promote reading classical texts: material explanation, group study, assessment, and team recognition. These stages were followed by awards or prizes to motivate the teams to continue striving for even greater achievements.